OUTCOMES OF DELAYED VS IMMEDIATE ANTIBIOTIC PRESCRIBING IN RESPIRATORY TRACT INFECTIONS. A SYSTEMATIC REVIEW - Munquith Mohammed; Abdullah Aliyan; Aida Emara; Alma Khaled Abdul Hamid Mansour; Fatima Zain Alabedin; Ameen Mustafa; Dana El Tayeb; Dania Al Mansi; Bayan Aliyan; Haneen Kamal Matar (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Respiratory tract infections (RTIs) are among the most common reasons for antibiotic prescriptions in primary care. However, concerns over antimicrobial resistance have led to increased interest in delayed antibiotic prescribing as a strategy to reduce unnecessary antibiotic use while maintaining clinical efficacy. The comparative outcomes of delayed versus immediate antibiotic prescribing remain a subject of debate, particularly concerning symptom duration, complications, and patient satisfaction.Objectives: This systematic review aims to evaluate and compare the outcomes of delayed versus immediate antibiotic prescribing in RTIs. Specifically, it examines the effects on symptom resolution, risk of complications, antibiotic consumption, adverse effects, and patient satisfaction.Methodology: A systematic review of published literature was conducted using databases such as PubMed, Cochrane Library, and Scopus. Studies included randomized controlled trials (RCTs), cohort studies, and systematic reviews published in peer-reviewed journals. The inclusion criteria were studies assessing outcomes of delayed versus immediate antibiotic prescribing for RTIs in primary care settings. Data extraction focused on symptom duration, antibiotic usage rates, complications, and patient-reported outcomes. A qualitative synthesis of the findings was performed to identify trends and patterns in the results.Results: The findings indicate that delayed antibiotic prescribing is associated with reduced overall antibiotic use without a significant increase in complications, such as pneumonia or otitis media. Patients in the delayed prescribing group reported similar symptom resolution times compared to those receiving immediate antibiotics. Additionally, delayed prescribing was linked to lower antibiotic-related adverse effects and comparable levels of patient satisfaction. However, variations in study designs and patient populations led to some discrepancies in reported outcomes.Conclusion: Delayed antibiotic prescribing for RTIs appears to be a viable strategy to reduce antibiotic consumption without compromising clinical outcomes. It is an effective approach to mitigate antimicrobial resistance while maintaining patient safety and satisfaction. Further high-quality studies are needed to explore long-term effects and optimize implementation strategies in different healthcare settings.